Artificial Intelligence Sparks Controversy in Content Marketing for Local Skincare Brands in Indonesia - Dewi Alesha Miller; Leliyana Andriyani (Yayasan Ilomata, 2026)
This study investigates the controversy and public response surrounding the use of artificial intelligence in content marketing by local skincare brands in Indonesia. While the adoption of AI-generated visuals has enabled faster content production and participation in digital trends, it has also provoked consumer backlash over concerns about authenticity, emotional connection, and the loss of artistic value. The research employed a qualitative netnographic approach. Data were collected from viral campaigns, social media commentary, and digital community discussions on public platforms such as Instagram and X (Twitter) between January and May 2025. The findings reveal that although AI accelerates content creation, its widespread use leads to visual uniformity and diminishes brand distinctiveness. Furthermore, Indonesian digital audiences actively shape brand narratives, demanding transparency, ethical standards, and respect for creative human work in marketing communications. The study highlights the need for brands to balance operational efficiency with cultural sensitivity and authentic engagement to build trust and long-term loyalty in the digital era. The main implication is that successful integration of AI in marketing requires open communication and a sustained commitment to human creativity. These insights offer valuable guidance for practitioners and policymakers seeking to navigate the ethical and cultural challenges of AI adoption in Indonesia’s dynamic beauty industry.